Mimosa pudica Modulates Neuroactive Ligand- Receptor Interaction in Parkinson’s Disease - Duyu, Taaza; Khanal, Pukar; Khatib, Nayeem Ashrafali; Patil, Basanagouda Mahadevagouda (Indian Journal of Pharmaceutical Education and Research, 2020)
Introduction: Mimosa pudica is scientifically reported for the enhancement of memory in multiple animal models including Parkinson’s disease (PD); however, the probable molecular mechanism for this effect has not been explained yet. The present study demonstrates the probable molecular mechanism to improve memory via in silico techniques. Materials and Methods: Phytoconstituents present in M. pudica and their targets involved in Parkinson’s disease were identified using open-source databases and published literature. Enrichment analysis of targeted proteins was identified using STRING, druglikeness of compounds was assessed using MolSoft and docking was carried using autodock4. Results: Out of twenty-seven phytoconstituents, seventeen modulated the proteins involved in the pathogenesis of PD. Norepinephrine was predicted to have the highest druglikeness score. The ADMET profiles revealed all phytoconstituents to be safe and are suitable for human consumption. Similarly, network analysis identified ADORA1 to be primarily targeted by phytoconstituents and luteolin was predicted to interact with maximum proteins. A docking study predicted quercetin and luteolin to possess the highest binding affinity with highly modulated protein ADORA1. Conclusion: M. pudica could primarily modulate neuroactive ligand receptor interaction followed by dopamine and serotonin synapses by regulating multiple proteins in PD.
Keywords: Luteolin; Mimosa pudica; Network pharmacology; Parkinson’s disease; Quercetin